JURIDICAL ANALYSIS OF WOMEN AS ABUSERS OF NARCOTICS CLASS I (ONE) TYPE OF SHABU (CASE STUDY OF DECISION NUMBER: 450/PID.SUS/2023/PN.MND) - K.Mahalieng, Abdul; Borman, Syahrul; Prawesthi, Wahyu; Astutik, Sri (Gapenas Publisher, 2025)
This thesis is titled